The geopolitics of climate change in Greenland: superpowers and small states - Freymann, E (2022)
This dissertation asks why and how Greenland became a focal point of U.S.–China competition between 2009 and 2021. The answer is climate geopolitics: the anticipated impact of long-term climate change on geography and its implications for national power, interest, and strategy. I posit that the anticipation of future climate change can have significant geopolitical consequences before the salient geophysical impacts actually arrive. Under certain conditions, this can give small polities substantial leverage to bargain for better outcomes. Taking Greenland as a case study, I show how the China and the United States conceptualize Greenland’s geographic significance in a future Arctic transformed by climate change. I then show how Greenland has exploited these perceptions to bargain for profit and autonomy. I discuss how this geopolitical dynamic shaped negotiations over three Chinese-proposed mega-deals with Greenland: to acquire land, build critical infrastructure, and operate a mine. Finally, I show that China is now extrapolating the logic of climate geopolitics to acquire access and influence in other climate-exposed island states: the Faroe Islands, Iceland, Maldives, and Kiribati. Analytic methods are discourse analysis and process-tracing. Sources include 36 elite interviews and government reports, company documents, academic papers, and newspaper articles in English, Chinese, and Danish.